The assessment of the effect of strength training of lower limbs on arching and forces distribution of the sole in young men - Bibro, Marta; Drwal, Aleksander; Jankowicz-Szymańska, Agnieszka (Health Promotion & Physical Activity, 2019)
Introduction: A human sole is an important element of the dynamic-static motor system, therefore its structure and function are often discussed in the literature. Many authors claim that the morphological structure of a foot adapts to some extent to its regular activity. There is an ongoing research of the effect of particular sports disciplines on the pattern of arching and loading of a foot. It has not been sufficiently documented whether a short intensive activity negatively affects existing abnormalities of the positioning of feet. Aim of the study: The aim of this research was the assessment of the effect of a 60-minute intensive strength training on the arching of a foot and the load of lateral and midial side of forefoot and hindfoot among young men. Material and methods: The research was carried out among 60 students between 19 and 26 years of age divided into 2 groups. The main research tool for assessing the arching and loading of particular parts of a foot was the BTS P-WALK baroresistant platform. The measurements were conducted over 30 seconds and contained the analysis in the static conditions after which it was repeated 60 minutes later. During that time Group 1 was carrying out a strength training consisting lower limb exercises, while group 2 was passively sitting down. Results: According to both measurements in the experimental group the side and central part of the foot were symmetrically loaded, However the loading of the forefoot significantly changed, especially in the forefoot centre. An hour long activity slightly affected the height of the arching in both feet, however for some of the participants there occurred the increase and among some the lowering of the middle long arch. These changes were not observed in the control group. Conclusions: An isolated, intensive strength training affects both the pattern of a foot loading and the length-wise arching of a feet.